2015
DOI: 10.1002/stem.2206
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Unique Subpopulation of Fibroblasts, Muse Cells, Ameliorates Experimental Stroke Possibly via Robust Neuronal Differentiation

Abstract: Objective: Muse cells reside as pre-existing pluripotent-like stem cells within the fibroblasts, are nontumorigenic, exhibit differentiation capacity into triploblastic-lineage cells, and replenish lost cells when transplanted in injury models. Cell fate and function of human skin fibroblast-derived Muse cells were evaluated in a rat stroke model. Methods: Muse cells (30,000), collected by pluripotent surface marker stage-specific embryonic antigen-3, were injected stereotaxically into three deposits within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
91
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 100 publications
(92 citation statements)
references
References 40 publications
1
91
0
Order By: Relevance
“…Studies have shown that MAP-2 expression was significantly increased during nerve injury, which represented reconstruction of dendritic structure to improve neurological function (Lin et al, 2015;Shafit-Zagardo et al, 2000;Uchida et al, 2015). MAP-2 is an important structural and functional protein found in the neuron bodies and dendrites for maintaining microtubule stability and nerve regeneration (Mohan and John, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that MAP-2 expression was significantly increased during nerve injury, which represented reconstruction of dendritic structure to improve neurological function (Lin et al, 2015;Shafit-Zagardo et al, 2000;Uchida et al, 2015). MAP-2 is an important structural and functional protein found in the neuron bodies and dendrites for maintaining microtubule stability and nerve regeneration (Mohan and John, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…11 In stroke model, they spontaneously differentiated into neuronal cells and participated in reconstruction of pyramidal tract, and in hepatectomy model, intravenously injected Muse cells differentiated into liver components after homing. 12,13 Since na€ ıve Muse cells were used in all these studies, Muse cells do not need to be induced into purposive cells prior to transplantation, unlike embryonic stem (ES) and induced pluripotent stem (iPS) cells. These unique performances are expected to be useful for regenerative medicine, while other functional aspect of Muse cells remains to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the adult tissue origin and the resemblance with many of the stem cell phenotypic features, bone marrow-derived stem cells have emerged as leading transplantable cell type for CNS disorders, including stroke [25]. Specialized subsets or populations, as well as engineered stem/progenitor cells, have been derived from the bone marrow, including mesenchymal stem or stromal cells (MSCs), endothelial progenitor cells (EPCs), SB623, multipotent adult progenitor cells (MAPCs), Multilineage-differentiating stress-enduring (Muse), among many others [2630]. Among these bone marrow-derived cells, MSCs have been extensively studied in stroke animal models.…”
Section: So Many Choices But We Need To Identify the Best Stem Cellmentioning
confidence: 99%